Development of a Science Learning Module using the Guided Discovery Method to Increase Learning Independence and Scientific Literacy Ability - Mashudi, Mashudi; Raharjo, Tri Joko; Kusmawan, Udan (Postgraduate, University of Mataram, 2024)
Science and technology are developing very quickly in the 21st century, especially in the field of education. Students need to be prepared to face these changes by having independent scientific literacy skills and skills that help them use technology. The findings from the 2015 PISA test are proof of the importance of scientific literacy in science learning. This research aims to evaluate the feasibility of the module, the effectiveness of the module, the profile of students' scientific literacy skills and learning independence after using the module and the differences in learning independence and scientific literacy before and after using the guided discovery-based module. This research uses research and development (R&D) methods modified from Borg & Gall in Sugiyono. The N-gain test is used to determine the effectiveness of the product, and descriptive data analysis is used to assess the feasibility and profile of students' scientific literacy abilities and learning independence. Differences in students' independence and scientific literacy abilities were analyzed using Kruskal-Wallis H test. The research results show that (1) the guided discovery-based module developed meets the content, presentation and language criteria very well; (2) The N-gain value with the criteria is experiencing an increase, in accordance with the results of the assessment of scientific literacy and student learning independence; (3) The profile of students' scientific literacy abilities which includes science context, competence and knowledge has moderate/good criteria; (4) The level of learning independence after using the module is at high criteria; (5) Students who use guided discovery-based modules can increase their scientific literacy and learning independence, but not at the same level as students who use traditional learning methods. This shows that the use of guided discovery-based modules developed as an alternative learning resource for science lessons regarding the water cycle is feasible to use